2019
DOI: 10.1128/aem.00156-19
|View full text |Cite
|
Sign up to set email alerts
|

Periphyton and Flocculent Materials Are Important Ecological Compartments Supporting Abundant and Diverse Mercury Methylator Assemblages in the Florida Everglades

Abstract: Mercury (Hg) methylation in the Florida Everglades is of great environmental concern because of its adverse effects on human and wildlife health through biomagnification in aquatic food webs. Periphyton and flocculant materials (floc) overlaying peat soil are important ecological compartments producing methylmercury (MeHg) in this ecosystem. These compartments retain higher concentrations of MeHg than did soil at study sites across nutrient and/or sulfate gradient(s). To better understand what controls Hg meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 62 publications
(102 reference statements)
1
19
0
Order By: Relevance
“…A wide occurrence of HgII methylating Deltaproteobacteria and Firmicutes was observed in periphyton collected in the Everglades (Bae et al, 2019). Because of the high abundance of macrophytes in shallow freshwater environments in tropical, subtropical and northern climates wetlands, macrophyte-associated periphyton were identified as contributors of MeHg production in these ecosystems (Hall et al, 2008) although their relative role in the lake Hg cycle remains largely unquantified.…”
Section: Primary Producers: An Important Niche For Hg Methylatorsmentioning
confidence: 99%
“…A wide occurrence of HgII methylating Deltaproteobacteria and Firmicutes was observed in periphyton collected in the Everglades (Bae et al, 2019). Because of the high abundance of macrophytes in shallow freshwater environments in tropical, subtropical and northern climates wetlands, macrophyte-associated periphyton were identified as contributors of MeHg production in these ecosystems (Hall et al, 2008) although their relative role in the lake Hg cycle remains largely unquantified.…”
Section: Primary Producers: An Important Niche For Hg Methylatorsmentioning
confidence: 99%
“…Consumption of contaminated fish esposes humans to this neurotoxin. Bae, Dierberg, and Ogram (2019) studied the distribution of mercury methylators in the Florida Everglades, United States. Jones et al (2019) used biochemical and molecular techniques to study the distribution of potential mercury methylators in two sulfate-impacted lakes on Minnesota's Mesabi Iron Range (USA).…”
Section: Annual Literature Reviewmentioning
confidence: 99%
“…The transformation of inorganic Hg into MMHg is mediated by anaerobic microorganisms ( Parks et al, 2013 ; Bravo and Cosio, 2020 ), predominantly from the Deltaproteobacteria, Methanomicrobia, and Firmicutes ( Christensen et al, 2016 , 2018 ). While significant work has examined Hg transformations in aquatic sediments ( Bae et al, 2019 ; Branfireun et al, 2020 ; Xiang et al, 2020 ), less research has focused on aquatic microbial biofilms like periphyton. Recent work demonstrates that these biofilms may harbor significant amounts of MMHg ( McDowell et al, 2020 ), but little is known about the community of microorganisms mediating Hg transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Mercury methylation in periphyton has been shown in many different ecosystems and has been attributed to sulfate-reducing bacteria (SRB) and methanogenic archaea that occupy anoxic niches within the periphyton biofilm structure ( Cleckner et al, 1999 ; Achá et al, 2011 ; Hamelin et al, 2011 ). To our knowledge, there is only one study that has identified Hg-methylating microorganisms in periphyton using the Hg methylation gene cluster, hgcAB , as a biomarker ( Bae et al, 2019 ). Bae et al (2019) found that periphyton and flocculant material from the Florida Everglades contained a diverse assemblage of hgcAB -containing microorganisms, including Deltaproteobacteria, Chloroflexi, Firmicutes, and Methanomicrobia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation